(untitled) (Constructionism Conference Proceedings, 2025)
This workshop presents an innovative approach to programming education, integrating storytelling, physical computing (micro:bit), and teamwork into a cohesive learning experience. Participants receive modular skill cards that serve as a flexible scaffolding, facilitating self-directed projects under a shared theme. This pedagogical strategy has been shown to promote creativity, collaboration, and peer-to-peer learning, while concurrently enhancing the appeal and accessibility of computer science education, particularly for novices and underrepresented groups such as girls. The workshop is grounded in the principles of constructionist and maker education, integrating block-based coding with tangible creation and storytelling to foster a motivating and inclusive environment for learners. Participants collaborate in teams to design unique projects, utilizing skill cards as a resource for guidance, examples, and support. The storytelling component encourages participants to contribute to a shared theme (e.g., a zoo) while pursuing individual goals, fostering ownership and engagement. The adaptable card system caters to diverse learning needs, promoting group interaction and peer support prior to teacher intervention. The efficacy of this format has been demonstrated through its successful implementation with teachers and students, highlighting its potential to enhance coding skills, motivation, and equity in STEM education. The workshop’s integration of technical skills with creativity and collaboration establishes a scalable model for inclusive and engaging computer science education that resonates with learners from diverse backgrounds.